Hakkari Belediye mezbahasında kesilen keçilerde sarcosporidiosis’in yaygınlığı - Aydın, Abdulalim; Göz, Yaşar (My University, 2013)
Bu çalışmada, 2010 yılının Mart ve Aralık ayları arasında Hakkari Belediye Mezbahasında kesilen ve 0- 5 yaşları arasında, 216 adet kıl keçisinin özefagusları sarcosporidiosis yönünden incelendi. Keçilerin 65 (%30.9)’inin özefagusunda makroskobik kistler, 210 (%97.22)’unda tripsin tekniği ile, 189 (%87.5)’unda ise serum fizyolojik muamele tekniği ile mikroskobik kistler tespit edildi. Tespit edilen makroskobik kistlerin tamamının Sarcocystis tenella’ya, 210 keçinin özefaguslarında görülen mikroskobik kistlerin 155 (%71.7)’inin Sarcocystis capracanis’e, 55 (%25.4)’inin S.tenella’ya ait olduğu görüldü. Keçiler için çok patojen olan S.capricanis’e yüksek oranda rastlanması (%71.7), yöredeki keçi yetiştiriciliği için Sarcosporidiosis’in önemli bir problem olduğunu göstermektedir.

In this study, the oesophagus of 216 hair goats between the age of zero and five slaughtering in Hakkari town's abattoir in the times between March and December in 2010 were investigated with regards to sarcosporidiosis. Macroscopic cysts were determined from oesophagus of 65 (30.9%) of goats. Microscopic cysts determined in the 210 (97.22%) of the goats in tripsin solution and the 189 (87.5%) of them in normal saline. It appeared that all macroscopic cysts observed in the goats were belonged to S.tenella, between the 210 microscopic cysts from oesophagus 155 (71.7%) of them belong to Sarcocystis capracanis and 55 (25.4%) of them belong to S.tenella. Finding S.capracanis, being very pathogen for goats, in high rate (71%) in the goats shows that sarcosporidiosis is an important problem for goat breeding in that area.
Prevalence of sarcosporidiosis in goats slaughtered at Hakkari town’s abattoir
Keywords: Veterinerlik